99mTc - MDP 골신티그라피를 이용한 Hydroxyapatite 안구 보충물의 혈관 신생 평가 및 임상적 유용성 - 최웅철; Woong Chul Choi; 김정훈; Jung Hoon Kim; 손형선; Hyung Sun Shon (Daihan angwa haghoi jabji, 2001)
안구 제거술 후 삽입한 hydroxyapatite 안구 보충물 내로의 혈관 신생 여부의 평가에 99mTc-MDP 골신티그라피의 임상적 유용성에 대해 알아 보고자 하였다. 안구 적출술과 변형된 안구내용물 제거술의 방법을 이용하여 안구 제거 후 hydroxyapatite 보충물을 삽입한 24명의 환자를 대상으로 하여 hydroxyapatite 보충물 삽입 후 3 ~33주 사이에 99 mTc-MDP 골신티그라피를 시행하였다. 검사 시기와 방사능 섭취의 등급 분류, 방사능 계수 비와 drilling 후 성공 여부와의 관계를 분석하였다. 방사능 섭취 정도를 육안적 분류 방법과 정량적 측정 방법에 의한 결과는 두 방법 모두 통계적으로 유의하였고 검사 시기와 방사능 계수 비 사이에 각각 유의한 상관관계가 있었으나 수술 방법에 따른 차이는 보이지 않았다. 안구 적출술과 안구 내용물 제거술의 수술 방법 차이에 관계없이 등급 2, 방사능 계수 비 1.56 이상인 경우에는 안구 고정술을 시행하여 좋은 결과를 기대할 수 있을 것으로 생각된다(한안지 42:313~320, 2001). This study was to evaluate the clinical usefulness of 99mTc-MDP bone scintigraphy for assessing vascular ingrowth into the ocular implants after enucleation and evisceration. Twenty four patients(M:F=7:17, mean age:36), with a coralline hydroxyapatite after uncomplicated enucleation or evisceration surgery were studied. Uptake ratio was also calculated by measuring the implants activity(H)and contralateral orbit activity(N). Grading score and uptake ratio were compared with clinical outcome of vascularization. Additionally, we also analyzed the vascularization status as time lapse between primary surgery and scintigraphic study and surgical methods. The degree of grade and uptake ratio were inversely correlated with vascular ingrowth. Higher than grade 2 or greater than 1.56 in H/N ratio seemed to be an indicator for better prognosis. 99mTc-MDP bone scintigraphy can be auseful method to evaluate the vascularized status of implants. Adequate time for 99mTc-MDP bone scintigraphy after enucleation and evisceration was 11~20 weeks(J Korean Ophthalmol Soc 42:313~320, 2001).